LIGHT CAPTURING WITHIN THE DEFECT LOCATED IN LINEAR ONE-DIMENSIONAL PHOTONIC LATTICE - Jovanović, Slavica; Stojanović Krasić, Marija (Bulletin of Natural Sciences Research, 2021)
Numerically investigated the light beam propagation through one-dimensional photonic lattice possessing one linear defect. It is shown how capturing of light depends on lattice characteristics as well as the width and wavelength of input light beam. Results may be useful for all-optical control of transmission of waves in interferometry.